2019
DOI: 10.2105/ajph.2018.304876
|View full text |Cite
|
Sign up to set email alerts
|

Need for Innovation in Public Health Research

Abstract: The recent conference Turning the Tide: A New Generation of Public Health Interventions highlighted the need to utilize innovative and emergent methodologies to confront increasingly complex public health challenges. In this commentary, we discuss three dominant themes from the conference: addressing multiple levels of causality in reducing health problems; technology-based methodologies to enhance health promotion; and improving translation and sustainment of effective health promotion programs. The subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…DiClemente, Nowara, Shelton, and Wingood () posit that new technologies may be equally, or possibly more, effective than old strategies and mobile technologies via the Internet and smartphones can potentially promote behaviour change. Baron et al () studied the implementation of a mobile phone application that allowed people with diabetes to transmit data to the healthcare provider and patients received timely feedback that identified any potential issues.…”
Section: New Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…DiClemente, Nowara, Shelton, and Wingood () posit that new technologies may be equally, or possibly more, effective than old strategies and mobile technologies via the Internet and smartphones can potentially promote behaviour change. Baron et al () studied the implementation of a mobile phone application that allowed people with diabetes to transmit data to the healthcare provider and patients received timely feedback that identified any potential issues.…”
Section: New Strategiesmentioning
confidence: 99%
“…Limited research was found about the use of online social media as a medium for improving self‐efficacy in patients with chronic disease, and Abroms () noted very little peer‐reviewed literature that looked at social media's influence on health; however, with the growing population of social media use, this could be a possible platform for sharing resources and supporting patients with chronic disease. DiClemente et al () call for a shift to technology‐based interventions as stand‐alone, or to supplement face‐to‐face or small group education, arguing that creating social networks for patients can foster continued adherence to health‐protective behaviours. Social media has been found to provide a space for patients with similar health issues to provide support for one another (Abroms, ; van Berkel et al, ).…”
Section: New Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the increase in obesity, society is experiencing the development of substantial technological advances. While it is true that the boom in new technologies could be involved in the increased availability of energy dense and processed foods as well as the growing prevalence of sedentary behaviors, it is also true that they could play an important role in the management of health problems [8] Interventions based on new technologies could be easily developed and accepted for the management of weight disorders, since they represent an interesting tool to increase individuals' awareness of the quantity and quality of food consumed and the physical activity performed [9] Additionally, lifestyle mobile health (mHealth) self-monitoring [10] appears to have a greater effect on self-efficacy, patient motivation and adherence to treatment, in such a way that it may elicit a greater weight loss than conventional methods [11]. A recent systematic review concluded that mHealth applications may represent an effective strategy for weight loss, and, since the review included both observational and experimental studies, the authors called for an update, including a meta-analysis, when the number of intervention studies allowed for the pooled effect size (ES) of the effect of mHealth applications on weight loss to be estimated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of technology is opening up new opportunities for health promotion [7,8]. A state of the art review depicted the area of fall prevention intervention technologies, reporting about the use of smartphones to enable older adults to self-assess and self-manage fall prevention [9].…”
Section: Introductionmentioning
confidence: 99%